Physiological and Yield Responses of Faba bean (Vicia faba L.) to Drought Stress in Managed and Open Field Environments. (4th December 2014) - Ammar, M. H.; Anwar, F.; El‐Harty, E. H.; Migdadi, H. M.; Abdel‐Khalik, S. M.; Al‐Faifi, S. A.; Farooq, M.; Alghamdi, S. S.
Abstract Water scarcity is threatening the sustainability of global food grain production systems. Devising management strategies and identification of crop species and genotypes are direly required to meet the global food demands with limited supply. This study, consisted of two independent experiments, was conducted to compare faba bean (Vicia faba L.) genotypes Giza Blanka, Goff‐1, Hassawi‐1, Hassawi‐2 and Gazira‐2 in terms of physiological attributes and yield under water‐limited environments. In first experiment, conducted in a growth chamber, osmotic stress of −0.78, −0.96, −1.19 and −1.65 MPa was induced using polyethylene glycol for 4 weeks. In second experiment, conducted in open field for two consecutive growing seasons, water deficit treatments were applied 3 weeks after sowing. In this experiment, irrigation was applied when an amount of evaporated water from the 'class A pan' evaporation reached 50 mm (well watered), 100 mm (moderate drought) and 150 mm (severe drought). Water deficit, applied in terms of osmotic stress or drought, reduced the root and shoot length, related leaf water contents, total chlorophyll contents and efficiency of photosystem‐II, plant height, grain yield and related attributes in faba bean; increased the leaf free proline, leaf soluble proteins and malondialdehyde contents, and triggered the maturity in tested faba bean genotypes. However, substantial genetic variation was observed in the tested genotypes in this regard. For instance, root length of genotypes Giza Blanka and Hassawi‐2 decreased gradually, whereas it was increased in genotypes Goff‐1, Hassawi‐1 and Gazira‐2 with increase in the level of osmotic stress. Genotypes Gazira‐2 and Hassawi‐2 had better relative leaf water contents, leaf free proline and soluble proteins under water deficit conditions; however, these were minimum in genotype Giza Blanka. Better accumulation of leaf free proline, soluble proteins, and maintenance of chlorophyll contents, tissue water, efficiency of photosystem‐II and grain weight in water‐limited conditions helped some genotypes like Hassawi‐2 to yield better. Future breeding programs for developing new faba bean genotypes for water‐limited environments may consider these traits.